Eksplorasi Sumber Pendanaan dan Investasi dalam Dunia Pendidikan - Zakina, Fadila Nur; takdirmin, Takdirmin; fitriani, Fitriani; Ramadhani Asri, Rahma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore various sources of funding and forms of investment in the education sector, both from the government, private sector, and non-profit institutions. The background of this study is based on the need for a sustainable and equitable education financing system, especially in the context of improving the quality and accessibility of education in Indonesia. A qualitative approach is used in this study with a literature study method. The results of the study indicate that there is great potential in diversifying education funding sources through public-private partnerships, education endowments, and outcome-based financing models. However, challenges such as transparency, accountability, and disparities in funding distribution are still major obstacles. This study recommends the need for more adaptive regulations and fiscal incentives to encourage sustainable investment in education. This research is expected to be the basis for formulating more inclusive and innovative education funding policies.